A Medicinal Halophyte Ipomoea pes-caprae (Linn.) R. Br.: A Review of Its Botany, Traditional Uses, Phytochemistry, and Bioactivity - Ganiyu Akinniyi; Jeonghee Lee; Hiyoung Kim; Joon-Goo Lee; Inho Yang (Marine Drugs, 2022)
Ipomoea pes-caprae (Linn.) R. Br. (Convolvulaceae) is a halophytic plant that favorably grows in tropical and subtropical countries in Asia, America, Africa, and Australia. Even though this plant is considered a pan-tropical plant, I. pes-caprae has been found to occur in inland habitats and coasts of wider areas, such as Spain, Anguilla, South Africa, and Marshall Island, either through a purposeful introduction, accidentally by dispersal, or by spreading due to climate change. The plant parts are used in traditional medicine for treating a wide range of diseases, such as inflammation, gastrointestinal disorders, pain, and hypertension. Previous phytochemical analyses of the plant have revealed pharmacologically active components, such as alkaloids, glycosides, steroids, terpenoids, and flavonoids. These phytoconstituents are responsible for the wide range of biological activities possessed by I. pes-caprae plant parts and extracts. This review arranges the previous reports on the botany, distribution, traditional uses, chemical constituents, and biological activities of I. pes-caprae to facilitate further studies that would lead to the discovery of novel bioactive natural products from this halophyte.